2017
DOI: 10.4314/evj.v21i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and antimicrobial susceptibility profiles of <i>Salmonella</i> isolates from dairy farms in and around Modjo town, Ethiopia

Abstract: Foodborne bacterial diseases are a serious challenge to human and animal health. Salmonella is a zoonotic foodborne pathogen and the etiologic agent of salmonellosis. A cross-sectional study was conducted from January 2016 to April 2016 on small scale and large scale dairy farms in and around Modjo town, Ethiopia. The main objectives of the study were to isolate and identify Salmonella from lactating cows, personnel's' and equipment at farms and to determine the in vitro antimicrobial resistance profiles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 23 publications
(22 reference statements)
7
18
7
Order By: Relevance
“…The microbial safety of these products is highly variable, as determined by bacterial foodborne pathogen occurrence; which poses a health risk to consumers. In the following sections, we report a summary of the literature review on the prevalence of four major bacterial foodborne pathogens ( Abera et al., 2016 , Abunna et al., 2017 ; Abunna et al., 2018a , Abunna et al., 2018b , Abunna et al., 2018c , Addis et al., 2011 , Adugna et al., 2015 , Adugna et al., 2013 , Banti, 2018 , Bedasa et al., 2018 , Desta, 2013 , Disassa et al., 2017 , Ejo et al., 2016 , Fisseha, 2017 , Garedew et al., 2015 , Gebretsadik et al., 2011 , Girma and Abebe, 2018 , Mekuria and Beyene, 2014 , Mengesha et al., 2009 , Molla et al., 2004 , Mossie and Dires, 2016 , Muhammed et al., 2013 , Mulaw, 2017 , Reta et al., 2016 , Seyoum et al., 2015 ; Tadesse and Dabassa, 2012 , Tesfaw et al., 2013 , Tesfay et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The microbial safety of these products is highly variable, as determined by bacterial foodborne pathogen occurrence; which poses a health risk to consumers. In the following sections, we report a summary of the literature review on the prevalence of four major bacterial foodborne pathogens ( Abera et al., 2016 , Abunna et al., 2017 ; Abunna et al., 2018a , Abunna et al., 2018b , Abunna et al., 2018c , Addis et al., 2011 , Adugna et al., 2015 , Adugna et al., 2013 , Banti, 2018 , Bedasa et al., 2018 , Desta, 2013 , Disassa et al., 2017 , Ejo et al., 2016 , Fisseha, 2017 , Garedew et al., 2015 , Gebretsadik et al., 2011 , Girma and Abebe, 2018 , Mekuria and Beyene, 2014 , Mengesha et al., 2009 , Molla et al., 2004 , Mossie and Dires, 2016 , Muhammed et al., 2013 , Mulaw, 2017 , Reta et al., 2016 , Seyoum et al., 2015 ; Tadesse and Dabassa, 2012 , Tesfaw et al., 2013 , Tesfay et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, fifteen peer-reviewed publications were identified and reviewed to summarise the prevalence of Salmonella spp. in Ethiopian milk and dairy products ( Abate et al., 2013 , Abera et al., 2016 , Abunna et al., 2017 , Abunna et al., 2018a , Abunna et al., 2018b , Addis et al., 2011 , Adugna et al., 2013 , Banti, 2018 , Ejo et al., 2016 , Mossie and Dires, 2016 , Mulaw, 2017 , Reta et al., 2016 , Tadesse and Dabassa, 2012 , Tesfaw et al., 2013 , Tesfay et al., 2013 ). In addition, two non-peer reviewed theses ( Dailey, 2011 , Hunduma, 2018 ) were identified as relevant but were not included in further analysis and data summary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations